Chemotherapy for Advanced Colorectal Cancer among Indonesians in a Private Hospital in Jakarta: Survival when Best Treatment is Given - Aru W Sudoyo; Ibrahim Basir; Levina Pakasi; Maureen Lukman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Background: Survival of colorectal cancer in Indonesia is thought to be shorter due to to several factors, among these: ethnic, nutritional, and the low affordability factors. Aim of this study to assess and evaluate survival in advanced colorectal cancer when given the best drugs available as recommended by international guidelines.Method: A historical cohort study was done in patients with advanced colon or rectal cancer between 2008 and 2010 at Medistra Hospital. Cases were retrieved from medical record data. Subjects were included if they were diagnosed or had a relapse of their disease during the study period and were followed until they died or lost to follow-up. Staging procedure was done using the tumor node metastasis (TNM) system. All patients received the combination of 5-uorouracil (5-FU)/leucovorin (LV), oxaliplatin for 6 cycles (FOLFOX4) as the standard  rst-line regimen for metastatic colorectal cancer (mCRC) in Indonesia. Oral capecitabine and targeted therapy such as bevacizumab and cetuximab might were also given, whenever indicated.Results: Nineteen patients (48.7%) died during the study period, while the rest were alive or lost to follow-up. The median overall survival of patients was 18 months (95% CI = 6.98 – 29.02 months). The longest survival was76 months (the patient is still alive when this manuscript was being prepared). Patients with colon cancer tended to live longer than rectal cancer, i.e. 21 vs. 15 months; log-rank p = 0.147. There was no signi cant difference of survival between patients with stage IV disease and relapse cases, i.e. 18 vs. 12 months, log-rank p = 0.807. Conclusion: With proper treatment and access to cytostatics and biologicals, advanced colorectal cancer among Indonesian patients have the same survival rates as patients in more developed countries as reported in the literature. Keywords: advanced colorectal cancer, chemotherapy, survival